3D PtFe Clusters with Cube‐in‐Cube Structure Enhance Oxygen Reduction Catalysis and Electrochemical Sensing. Issue 12 (17th May 2018) - Lin, Fei; Sun, Yingjun; Lai, Jianping; Wang, Kai; Tang, Yonghua; Chao, Yuguang; Yang, Yong; Feng, Jianrui; Lv, Fan; Zhou, Peng; Huang, Minghua; Guo, Shaojun
Abstract: Rational design and construction of high‐performance electrocatalytic nanomaterials is significant for improving activity and stability of oxygen reduction reaction (ORR), and the sensitivity and selectivity of electrochemical sensors. Herein, the synthesis of a class of PtFe clusters with a cube‐in‐cube structure (PtFe‐CIC) is reported. The nanoscale PtFe clusters are constructed by primary subunits of the nanocube and have porous structure and high surface area. The PtFe‐CIC exhibits much enhanced electrocatalytic activity for ORR by showing high specific activity and mass activity. The PtFe‐CIC is a highly universal and efficient electrocatalyst for boosting the electrocatalysis of H2 O2 and hydrazine to construct high‐sensitivity sensors in 0.1m phosphate‐buffered saline solution. The as‐prepared PtFe‐CIC shows a wide detection range of 2 × 10 −9 to 1.5 × 10 −3 m for H2 O2 with a very low detection limit of 0.7 × 10 −9 m, and a wide linear range of 0.1–357.9 × 10 −6 m for hydrazine with a very low detection limit of 33 × 10 −9 m . This work opens a new way to design 3D superarchitectures with porous structure for boosting electrocatalysis of small molecules. Abstract : PtFe clusters with a cube‐in‐cube structure (PtFe‐CIC) are synthesized and are shown to exhibit high electrocatalytic performance for oxygen reduction reaction. They are also highly universal and efficient electrocatalysts for boosting the electrocatalysis of H2 O2 and hydrazine to construct high‐sensitivity sensors.